The Effects of Mergers and Acquisitions on Shareholder’s Value: Evidence from UK-based Pharmaceutical Companies. - Bader, Izzat (2013)
Due to advancements in globalization, mergers and acquisitions have been on an increasing trend over the past few decades. More, specifically, various factors have influenced the pharmaceutical industry, prompting it towards takeovers as a form of salvation. By addressing the concept of “patent cliffs”, where blockbuster drugs lose their patents at a rapid pace, acquiring firms in this industry anticipate that such deals could patch up gaps in their research and development. Being an issue of great controversy, mergers and acquisitions have been argued amongst consultants, economists as well as financial organizations as to determine the effect these have on firms.